Pengembangan Video Animasi Materi Gerak Benda untuk Meningkatkan Kemampuan Berpikir Kreatif - Damaiyanti, Ade; Andriani, Dwi; Bunayya, Haikal Wafi; Ritonga, Susi Febriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to enhance students' creative thinking abilities in science subjects with the topic of motion through the use of animated video media. The research method used is the Research and Development approach. The study employed data collection techniques such as expert validation of media and materials, as well as pretests and posttests. The research results indicate a significant improvement in student responses between the pretest and posttest. The average score for the pretest was 60%, while the average score for the posttest was 81.53%. Therefore, it can be concluded that the development of animated video media can enhance students' creative thinking abilities.